2003
DOI: 10.1002/prot.10401
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent dyes as probes to study lipid‐binding proteins

Abstract: We studied the equilibrium binding of two hydrophobic fluorescent dyes, ANS and bisANS, to four members of a family of intracellular lipid-binding proteins: IFABP, CRABP I, CRABP II, and ILBP. The spectral and binding parameters for the probes bound to the proteins were determined. Typically, there was a single binding site on each protein for the ligands. However, IFABP cooperatively bound a second bisANS molecule in the binding pocket. Comparative analysis of affinities and spectral characteristics for the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 29 publications
2
33
0
Order By: Relevance
“…To establish an assay system that can easily distinguish the open/ close structures of LolA and LolA(R43L), we examined the binding of some fluorescent probes and found that the binding of bis-ANS was significantly different between LolA and LolA(R43L). The fluorescence of bis-ANS has been reported to significantly increase when it binds to a hydrophobic environment (16). The fluorescence intensity of bis-ANS was very low in the absence of LolA proteins (Fig.…”
Section: Structure Of the Lola(r43l) Derivative-two Forms Ofmentioning
confidence: 91%
“…To establish an assay system that can easily distinguish the open/ close structures of LolA and LolA(R43L), we examined the binding of some fluorescent probes and found that the binding of bis-ANS was significantly different between LolA and LolA(R43L). The fluorescence of bis-ANS has been reported to significantly increase when it binds to a hydrophobic environment (16). The fluorescence intensity of bis-ANS was very low in the absence of LolA proteins (Fig.…”
Section: Structure Of the Lola(r43l) Derivative-two Forms Ofmentioning
confidence: 91%
“…Fluorometric titrations of ANS into L-FABP were performed as previously described [26]. BisANS was used as the binding cavity probe for human I-BABP [27]. The binding properties of PPAR␥LBD were measured by titration with the fluorescent FA cis-parinaric acid as previously described [28].…”
Section: Ligand Binding Fluorescence Measurementsmentioning
confidence: 99%
“…The ligand binding affinities of each protein were measured using the fluorescent probes ANS (L-FABP binding measurements), cisparinaric acid (PPAR␥LBD binding measurements) and bisANS (I-BABP binding measurements), that have previously been shown to bind specifically in the lipid binding cavity of these proteins [26][27][28]. The binding data indicated the proteins did not have an appreciable affinity for the fluorescent probes before delipidation, again suggesting endogenous lipids remain protein-bound Fluorescence was normalized as a relative binding, with no-competition (relative binding = 1) and full competition (relative binding = 0).…”
Section: Ligand Binding Measurements To Access Protein Functionality mentioning
confidence: 99%
See 1 more Smart Citation
“…The compound 1,8-ANS is a widely employed fluorescent probe that noncovalently attaches to the hydrophobic cavities and/or clefts on protein surfaces and are commonly used to monitor solvent exposed hydrophobic patches as well as protein unfolding mechanism (Cardamone and Puri, 1992;Hawe et al, 2008;Pastukhov and Ropson, 2003;Uversky et al, 1996). fluorescence intensity can also be detected (Hawe et al, 2011).…”
Section: Discussionmentioning
confidence: 99%